2018
DOI: 10.1073/pnas.1812915116
|View full text |Cite
|
Sign up to set email alerts
|

DeltaNp63-dependent super enhancers define molecular identity in pancreatic cancer by an interconnected transcription factor network

Abstract: Molecular subtyping of cancer offers tremendous promise for the optimization of a precision oncology approach to anticancer therapy. Recent advances in pancreatic cancer research uncovered various molecular subtypes with tumors expressing a squamous/basal-like gene expression signature displaying a worse prognosis. Through unbiased epigenome mapping, we identified deltaNp63 as a major driver of a gene signature in pancreatic cancer cell lines, which we report to faithfully represent the highly aggressive pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 68 publications
5
79
0
Order By: Relevance
“…Thus, it is possible that the ability of ZBED2 to modulate the transcriptional output of IRF TFs may extend to its ability to regulate stem cell function and cell identity within normal squamous epithelial tissues. Similar to ZBED2, prior studies have implicated TP63 and GLI2 as additional determinants of squamous cell identity in PDA (10,11,13,15). Our analysis has shown that ZBED2 and TP63 are among the most aberrantly expressed TFs in the squamous subtype of PDA, however these two TFs are not expressed in a mutually exclusive manner.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, it is possible that the ability of ZBED2 to modulate the transcriptional output of IRF TFs may extend to its ability to regulate stem cell function and cell identity within normal squamous epithelial tissues. Similar to ZBED2, prior studies have implicated TP63 and GLI2 as additional determinants of squamous cell identity in PDA (10,11,13,15). Our analysis has shown that ZBED2 and TP63 are among the most aberrantly expressed TFs in the squamous subtype of PDA, however these two TFs are not expressed in a mutually exclusive manner.…”
Section: Discussionsupporting
confidence: 61%
“…While PDA is defined by its histopathological resemblance to ductal epithelial cells of the exocrine pancreas, studies in mice have shown that acinar cells can serve as a cell-of-origin of this disease, which trans-differentiate into the ductal fate following acquisition of a Kras activating mutation (3)(4)(5). At later stages of tumor development, aberrant up-regulation or silencing of master regulator transcription factors (TFs) in PDA can lead to reprogramming of ductal identity towards that of other cell lineages, including mesenchymal (6)(7)(8), foregut endodermal (9), or squamous epithelial fates (10)(11)(12). While each of these lineage transitions are capable of promoting disease progression in experimental systems, only the presence of squamous characteristics correlates with a shorter overall survival in human PDA patients (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have defined a mechanism by which tumor cells gain an ability to reprogram their local microenvironment through the acquisition of TP63 expression, which is a master regulator of the squamous subtype of PDA (Hamdan and Johnsen, 2018;Somerville et al, 2018). Mechanistically, we have shown that TP63 activates a pro-inflammatory secretory phenotype that triggers iCAF induction through an IL-1α-dependent signaling mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…The functional relevance of squamous trans-differentiation in pancreatic cancer was unclear until recently, when studies from several laboratories, including our own, demonstrated that the transcription factor TP63 (delta N isoform, hereafter referred to as TP63 for simplicity) is the master regulator of the adenosquamous phenotype in PDA (Andricovich et al, 2018;Hamdan and termed iCAFs, have low expression of myCAF markers and instead produce high levels of inflammatory cytokines, such as IL-6, CXCL1, and LIF (Öhlund et al, 2017). Although the iCAF/myCAF ratio, the extent of neutrophil infiltration, and the overall level of stromal inflammation can vary significantly between PDA patients, the underlying features of cancer cells that drive these differences are only beginning to be understood (Vennin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example LV 24 was found to be an important feature for classifying MPNST tumor samples but not the other benign tumor samples ( Figure 3Biii). LV 24 significantly associated with the ΔNp63 pathway (FDR < 0.05), a pathway with implications in determining malignancy and poor survival in various subtypes of pancreatic and squamous cell carcinomas [47] . ΔNp63 signaling in the central nervous system is believed to play a role in neural precursor cell survival and neural stem cell dynamics [48,49] , but its role in formation or maintenance of malignant NF1 tumors like MPNSTs is relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%